The formation of the mixed anions PAsO7 in solid solutions Mg2P2O7 —Mg2As2O7 - Mazhenov, N.A.; Syzdykova, Z.R. (KU Publ., 2022)
The article presents structural features at formation of solid solutions of the isostructural Mg2P2O7 and Mg2As2O7 connections. In these compounds, complex Р2О7 4- anions, As2O2 4- , as well as the formation of complex PAsO7 4 anions, is not natural. The formation of solid solutions is confirmed by the linear dependence of x-ray debaegram and optical refractive indices, depending on the concentration of P/As. In the article, phosphates are involved in energy processes in cells. For the first time, the formation of mixed anions in polyphosphates has been proven. The oscillatory spectra of pyro anions have intervals of localization of terminal and bridging groups of atoms that have no intersection regions. Strip at 662–670 cm-1 (between structures from P: As=0.8:0.2 to 0.1–0.9), located between vsPOP frequency in ᵦ — Mg2P2O7 at 737 cm-1 and the frequencies about 550 cm-1 characteristic of fluctuations of vsAsOAs in alkaline pyroarsenates, is interpreted as a strip of fluctuations of vsPOAs of the mixed PAsO7 ions. In the area, the strip at 925–902 cm-1 is located between frequencies of fluctuations of vasPOP and vasAsOAs. The fluctuations of mastic group P-O found in ranges of infrared absorption allow establishing knowledge of the adjacent anions (PAsO7)4- that it is possible to confirm with quantum-chemical calculations in the subsequent.
Mg2Р2О7 — Mg2As2O7 қатты ерітінділерде PASO7 аралас аниондарының пайда болуы
Образование смешанных анионов в PAsO7 в твердых растворах Mg2Р2О7 — Mg2As2O7
Keywords: pyrophosphate; pyroarsenate; debaegram; empirical; refractometric; valence-force field; linear approximation